Penggunaan Kartu Huruf untuk Meningkatkan Kemampuan Menulis Permulaan Siswa Tunagrahita - Yesi Oktavia Ayu Wulandari; Umi Safiul Ummah; Yudi Tri Harsono (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2015)
The research was aim at describing the students’ ability to write for starters in the second grade of intellectual disability before and after using a flashcard, as well as to analyze the effect of media use the letter cards toward students’ ability to write for starters. This research was usingQuasi Experiment with model One Group – Pre-test – Post-test Design. The results of data analysis wasthe use of flashcards, the ability to write for starters of students categorized as less. Results of the average value of pre-test amounting to 47.After using flashcard, they experiencedan increase of to write for starters ability. Results of the averange value of post-test amounting to 82. Conclusion from the research was the use of flashcard media can improvestudents to write for stater of intellectual disability.Penelitian ini bertujuan mendeskripsikan abilitas menulis permulaan siswa tunagrahita sebelum dan setelah menggunakan kartu huruf, serta menganalisis pengaruh penggunaan kartu huruf terhadap abilitas menulis permulaan. Penelitian ini menggunakan metode eksperimen, desain Quasi Experiment dengan model: One Group – Pre-test – Post-test Design. Hasil dari analisis data sebelum menggunakan kartu huruf, abilitas menulis permulaan siswa dikategorikan kurang. Hasil yang rata-rata nilai pre-test sebesar 47. Setelah menggunakan kartu huruf, terjadi peningkatan abilitas menulis permulaan. Hasil rata-rata nilai post-test sebesar 82. Penelitian ini menunjukkan bahwa abilitas menulis permulaan siswa tunagrahita dapat ditingkatkan dengan media kartu huruf.